PENGARUH KOMUNIKASI TERHADAP KINERJA PEGAWAI - Jimmi Hijrah Sitompul; Dewi Zahra; Amrijal Pulungan; Irsanuddin Harahap (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
It is important to know the effect of communication on employee performance at PT. Harapan Bersama Lestari Medan. The data collection method is used in research with a survey approach through observation, interviews, questionnaires and documentation studies. The data analysis method used is multiple linear regression analysis. The population in this study were part of the employees of PT. Harapan Bersama Lestari Medan, with a total of 38 employees. The results of the study are simultaneous communication variables have a significant effect on employee performance, partially communication variables do not significantly influence employee performance, the value of the multiple correlation coefficient (R) is 0.718, this indicates that the magnitude of the influence of the communication variable on employee performance is 0.718 or (71.8%), that the value of the coefficient of determination (R2) is 0.516. This shows that the magnitude of the influence of the communication variable on employee performance is 0.516 or (51.6%) and the remaining 0.484 or (48.4%) is influenced by other factors or variables.